Bariatric surgery: behavioral patterns and personality disorders in the preoperative period - Michelle Diniz da Mata; Samuel Barroso Rodrigues; Camila Souza de Almeida; Sebastião Júnior Henrique Duarte; Ricardo Bezerra Cavalcante; Richardson Miranda Machado (Universidad de Santander, 2024)
Introduction: Bariatric surgery has become an increasingly common procedure, especially for patients with morbid obesity who have obtained unsatisfactory results from conventional treatments. Objective: To evaluate the occurrence of behavioral patterns and personality disorders in patients in the preoperative period of bariatric surgery. Materials and methods: Cross-sectional study carried out with 146 patients from a medium-sized clinic, a reference in the execution of bariatric surgeries in the Midwest region of Minas Gerais, Brazil. Data collection was performed using the psychological instrument entitled Factorial Personality Battery. Descriptive analysis and data association were performed. Results: Half of the participants presented high or very high scores for greater propensity to develop depression and anxiety, showing a close relationship with personality disorders, especially with behavioral patterns of effort and dedication. Discussion: The patterns of effort and dedication behavior are protective factors in the postoperative period, taking into account the adaptations and new habits necessary for a good recovery and maintenance of weight loss. Conclusions: The dysfunctional patterns of behavior that stood out most are related to greater difficulty in perceiving the positive side and ease in perceiving the negative side, leading to a more intense experience of suffering, in addition to difficulty in making decisions and facing routine challenges. Screening behavioral patterns and personality disorders preoperatively is necessary for adequate patient monitoring and successful bariatric surgery.